Micro and Nanofabrication : Is a Practical Three-Dimensional Cell Culture Platform for Drug Discovery Achievable? - Wu, Ze-Zhi; Kisaalita, William S. (International Journal of Medical Nano Research, 2015)
Direct and indirect evidence, in support of the notion that biological activity of three-dimensional (3-D) cultures may more closely mirror what happens in vivo, has appeared in the literature for the past three decades. This is probably best exemplified in the field of experimental oncology that adopts 3-D multicellular tumor spheroids (MCTS) to mimic the in vivo situation. Early seminal work in this section was represented by Sutherland and colleagues who used MCTS as an in vitro model for systematic studies on tumor cell responses to therapeutic treatments [1]. Multicellular spheroids have been able to fully recapitulate the multicellular mediated drug resistance of EMT6 tumors, which was inherently induced in vivo but completely lost when cancer cells were dissociated and cultured as monolayers. It has been shown that the phenotypic transformation of malignant cells in a 3-D collagen gel configuration is achievable upon treatment with integrin antibodies, while this has never been possible in monolayer cultures. Researchers have also noted that HT-1080 fibrosarcoma and MDA-MB-231 carcinoma cells showed protease independent amoeboid movement within 3-D collagen matrix while, in 2-D cultures, this movement is totally dependent on proteases like matrix metalloproteinases. This challenges the traditional screening for anti-metastatic agents against proteolytic activity with 2-D monolayer cultures. In fact, Mueller-Klieser [2] has actually proposed that 3-D spheroids should become mandatory test systems in cancer therapeutic screening programs.